1986
DOI: 10.1007/bf02057901
|View full text |Cite
|
Sign up to set email alerts
|

Events in degenerating cat peripheral nerve: Induction of Schwann cell S phase and its relation to nerve fibre degeneration

Abstract: Severance of a peripheral nerve leads to a characteristic series of events in the distal stump, including the dissolution of axons and myelin and the proliferation of Schwann cells within their basal lamina. This study examines the relationship between the spatial-temporal pattern of the induction of the Schwann cell S phase, loss of the structural and functional properties of axolemma, and the clearance of myelin debris in the cat tibial nerve. Nerve transection stimulated a monophasic increase in [3H]thymidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 36 publications
4
65
0
Order By: Relevance
“…In adults Schwann cell death occurs much later, usually after several months. Studies of adult animals that followed Schwann cells for only a few after axotomy found little death, whereas studies in rodents and in man that extended for several months of denervation (Ebenezer et al, 2007;Pellegrino et al, 1986;Sulaiman et al, 2002) identified extensive Schwann cell loss.…”
Section: Death Of Denervated Schwann Cellsmentioning
confidence: 99%
“…In adults Schwann cell death occurs much later, usually after several months. Studies of adult animals that followed Schwann cells for only a few after axotomy found little death, whereas studies in rodents and in man that extended for several months of denervation (Ebenezer et al, 2007;Pellegrino et al, 1986;Sulaiman et al, 2002) identified extensive Schwann cell loss.…”
Section: Death Of Denervated Schwann Cellsmentioning
confidence: 99%
“…Establishment of this supportive microenvironment requires that nerve undergo the morphological changes of Wallerian degeneration (Holmes and Young, 1942;Fawcett and Keynes, 1990;Tonge and Golding, 1993), in which axon segments and myelin distal to a site of trauma degenerate (Holmes and Young, 1942) and are phagocytosed by Schwann cells and macrophages (Perry and Brown, 1992). Coincident with axonal degeneration, normally quiescent Schwann cells dedifferentiate and proliferate, an event critically important for the promotion of axonal regeneration (Hall and Gregson, 1977;Pellegrino et al, 1986;Fawcett and Keynes, 1990;Nadim et al, 1990). Thus, identification of the signals regulating Schwann cell dedifferentiation, proliferation, and migration during Wallerian degeneration is of great interest.…”
Section: Abstract: Neuregulins; Glial Growth Factor; Schwann Cell; Ementioning
confidence: 99%
“…Although the induction of Schwann cell DNA synthesis in surgically transected sciatic nerve has been carefully analyzed in the adult mouse (Bradley and Asbury, 1970) and cat (Pellegrino et al, 1986;Oaklander et al, 1987), a similar detailed analysis of postaxotomy Schwann cell mitotic indices in the rat has not been performed (Friede and Johnstone, 1967). Because it is well recognized that there are species-specific temporal variations in the onset and peak of Schwann cell mitogenesis (Lubinska, 1964), it was necessary that we establish these parameters for the rat.…”
Section: Induction Of Schwann Cell Dna Synthesis In Axotomized Sciatimentioning
confidence: 99%
“…Nerve disease and injury, including nerve transection and demyelination, prompt Schwann cells to enter cell cycle (Friede and Johnstone, 1967;Pellegrino and Spencer, 1985;Griffin et al, 1987Griffin et al, , 1990Oaklander et al, 1987b;Cheng and Zochodne, 2002). The factors that signal this proliferation are not fully understood (Pellegrino et al, 1986;Oaklander and Spencer, 1988;Clemence et al, 1989). The Schwann cells of individual degenerating nerve fibers divide (Pellegrino et al, 1986;Oaklander et al, 1987a), and an attractive speculation has been that axonal degeneration results in either degradation or release of axolemmally bound neuregulins (Ratner et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The factors that signal this proliferation are not fully understood (Pellegrino et al, 1986;Oaklander and Spencer, 1988;Clemence et al, 1989). The Schwann cells of individual degenerating nerve fibers divide (Pellegrino et al, 1986;Oaklander et al, 1987a), and an attractive speculation has been that axonal degeneration results in either degradation or release of axolemmally bound neuregulins (Ratner et al, 1986). However, Wallerian degeneration produces a variety of other changes throughout the nerve distal to the site of injury, including opening of the blood-nerve barrier (Weerasuriya, 1988;Bouldin et al, 1990Bouldin et al, , 1991 and recruitment of circulating monocytes (Beuche and Friede, 1984;Stoll et al, 1989;Avellino et al, 1995).…”
Section: Introductionmentioning
confidence: 99%